ok im having a bit of trouble with interpreting this question:
Show that: 3x + 2/x+1 = 3 - (1/x+1)
You could do $\displaystyle \frac{3x+2}{x+1}$ using polynomial long division.
Or you could assume that the result will be of the form $\displaystyle A + \frac{B}{x+1}$ and solve for A and B.
Or you could do some fancy re-arranging:
$\displaystyle \frac{3x+2}{x+1} = 3\, \left(\frac{3x+2}{3(x + 1)}\right)$
$\displaystyle = 3\, \left(\frac{3x+2}{3x + 3}\right) = 3\, \left(\frac{(3x+3)-1}{3x + 3}\right)$
$\displaystyle = 3\, \left(1 - \frac{1}{3x + 3}\right) = 3 - \frac{1}{x + 1}$.